Surgical versus Nonsurgical Management of Postmastectomy Lymphedema: A Prospective Quality of Life Investigation - Darrach, Halley; Yesantharao, Pooja S.; Persing, Sarah; Kokosis, George; Carl, Hannah M.; Bridgham, Kelly; Seu, Michelle; Stifler, Samantha; Sacks, Justin M. (Journal of Reconstructive Microsurgery, 2020)
Background Postmastectomy secondary lymphedema can cause substantial morbidity. However, few studies have investigated longitudinal quality of life (QoL) outcomes in patients with postmastectomy lymphedema, especially with regard to surgical versus nonoperative management. This study prospectively investigated QoL in surgically versus nonsurgically managed patients with postmastectomy upper extremity lymphedema.Methods This was a longitudinal cohort study of breast cancer-related lymphedema patients at a single institution, between February 2017 and January 2020. Lymphedema Quality of Life Instrument (LyQLI) and RAND-36 QoL instrument were used. Mann–Whitney U and Fisher's exact tests were used for descriptive statistics. Wilcoxon's signed-rank testing and linear modeling were used to analyze longitudinal changes in QoL.Results Thirty-two lymphedema patients were recruited to the study (20 surgical and 12 nonsurgical). Surgical and nonsurgical cohorts did not significantly differ in clinical/demographic characteristics or baseline QoL scores, but at the 12-month time point surgical patients had significantly greater LyQLI overall health scores than nonsurgical patients (79.3 vs. 58.3, p = 0.02), as well as higher composite RAND-36 physical (68.5 vs. 38.3, p = 0.04), and mental (77.0 vs. 52.7, p = 0.02) scores. Furthermore, LyQLI overall health scores significantly improved over time in surgical patients (60.0 at baseline vs. 79.3 at 12 months, p = 0.04). Besides surgical treatment, race, and age were also found to significantly impact QoL on multivariable analysis.Conclusion Our results suggest that when compared with nonoperative management, surgery improved QoL for chronic, secondary upper extremity lymphedema patients within 12-month postoperatively. Our results also suggested that insurance status may have influenced decisions to undergo lymphedema surgery. Further study is needed to investigate the various sociodemographic factors that were also found to impact QoL outcomes in these lymphedema patients.
Keywords: lymphedema; surgery; quality of life; RAND-36; LyQLI